Some Fixed Points Results of Quadratic Functions in Split Quaternions - Young Chel Kwun; Mobeen Munir; Waqas Nazeer; Shin Min Kang (Journal of Function Spaces)
We attempt to find fixed points of a general quadratic polynomial in the algebra of split quaternion. In some cases, we characterize fixed points in terms of the coefficients of these polynomials and also give the cardinality of these points. As a consequence, we give some simple examples to strengthen the infinitude of these points in these cases. We also find the roots of quadratic polynomials as simple consequences.